Promoting Alternative Finance for SMEs in Uganda - Bakunda, Geoffrey; Walusimbi-Mpanga, George; Munaabi, Yvonne; Kawule Jooga, Ronald; Kugonza, Faith (TrustAfrica, 2013)
This policy brief outlines policy actions the Government of Uganda, and other stakeholders, can take to help mitigate the perennial problem of limited access to finance by small and medium-sized enterprises (SMEs). It also outlines policy actions necessary to improve the SMEs’ ability to forge effective business linkages with large FDI firms.